Ace Up One's Sleeve: A Systematic Communicative Review of Journalistic Media Dominance in Shaping the Contemporary Political Landscape - Siregar, Rahman; Saragih, Muhammad Yoserizal (International Journal of Social Science, Education, Communication and Economics, 2024)
This article aims to analyze the role of journalistic media in shaping the contemporary political landscape, focusing on its ability to manipulate and direct public opinion and policy. Considering the media's dominance in agenda setting, this study highlights the urgency of understanding its broad influence on democracy and public policy. Journalistic media, which has transformed from a passive information provider to an active opinion shaper, plays a crucial role in this fast-paced and widespread information era. Therefore, a deep understanding of how media shapes political narratives is essential to maintaining the integrity of the democratic process. The methodology used in this research is a Systematic Literature Review (SLR), which involves the collection and analysis of data from previously published sources to build a comprehensive understanding of the media's role in politics. This approach allows for the identification of trends, challenges, and the broader impact of media on politics. Additionally, this study employs theoretical analysis by combining Media Dependency Theory and Agenda Setting Theory to examine how public dependence on media and media's power in setting the agenda influence political dynamics. The results of the study indicate that media often leverages its strategic position to direct public opinion, which can significantly impact election outcomes and public policy. The high public dependence on media for information makes the media a powerful tool in shaping the political agenda, often benefiting media owners or specific interest groups. Based on the findings and discussion, this article recommends the need for stricter media oversight and increased media literacy among the public to reduce bias and ensure that the media plays its role as an effective watchdog rather than a biased opinion shaper. These recommendations aim to support policies that promote transparency and integrity in journalism, ensuring that the media can continue to be a pillar of healthy democracy without compromising objectivity or accountability.